PENERAPAN PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING UNTUK MENINGKATKAN PEMAHAMAN KONSEP SISWA PADA PELAJARAN IPA MATERI POKOK GAYA - Nurjanah, Annisa (2014)
Science subjects are subjects which have been considered difficult by most students, ranging from primary school to secondary school. Implementation science learning centered only on textbooks alone, so as not fully embedded in the students' understanding of science concepts. This occurs because the implementation does not emphasize learning science students to be active and creative. In the process of learning science teachers can choose the right model to use in the implementation of active learning and creative science. The purpose of this research is to investigate the implementation of contextual teaching and learning models in science subject matter force at the fourth grade students of SDN 5 Cikidang and to improve the understanding of the concept after learning apply contextual teaching and learning in science subject matter force in grade IV SDN 5 Cikidang. The method used in this study are three action research cycles. The results of the implementation of learning and increased understanding of science concepts retrieved by using sheet test (post-test), observation sheets, and documentation. The results showed an increase in students' understanding of concepts followed by an increase in the implementation of learning. Increase students' understanding of the concept as applied to models of contextual teaching and learning. Based on the average value of students showed that an increase in understanding of concepts in each cycle, the first cycle resulted in the percentage of the average value of 59.43%, the second cycle resulted in a percentage of means were 63.14%, and the third cycle produces average percentage values -rata 71.14%. Based on the results of this study concluded that learning by applying the model of contextual teaching and learning can improve the understanding of the concept of fourth grade students of SDN 5 Cikidang.